Rekomendasi Laptop Gaming High end untuk Gamer Professional dengan Elimination Et Choix Traduisant la Realite (ELECTRE) - Arisawati, Ester; Rinawati, Rinawati; Handayanna, Frisma; Sihombing, Erene Gernaria; Dewi, Linda Sari (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
The purpose of this research is as a recommendation tool in determining high end gaming laptops for professional gamers by using a decision support system. The settlement method used in this study is Elimination Et Choix Traduisant la Realite (ELECTRE). The data collection techniques were carried out randomly by conducting observations, interviews and questionnaires to 250 respondents (gamers) and 10 computer shops in the district of Simalungun. In this study, using five alternatives, among others: Asus ROG G703 (A1), Razer Blade Pro (A2) MSI GT75VR Titan-083 (A3), Acer Predator Triton 700 (A4), Alienware 17 (A5) and five assessment criteria, among others: Price (C1), Processor Type (C2), RAM Capacity (C3), VGA Card Type (C4) and Hard Drive (C5). The results of the Elimination Et Choix Traduisant la Realite (ELECTRE) method recommend the Predator Triton 700 (A4) alternative as the first recommendation for the selection of high end gaming laptops for professional gamers.